1996
DOI: 10.1152/ajpheart.1996.270.1.h358
|View full text |Cite
|
Sign up to set email alerts
|

Flow velocity of single lymphatic capillaries in human skin

Abstract: The purpose of this study was to investigate the previously unknown flow velocity in single lymphatic capillaries of humans in the supine position. Fifteen healthy subjects (10 women and 5 men; mean age 35.8 +/- 13.1 yr) were studied. Ten microliters of fluorescein isothiocyanate-dextran (150,000 mol wt) were injected into the subepidermal layer of the foot dorsum. The filling of the microlymphatics from the resulting depot was visualized by fluorescence video microscopy and stored on videotape. Flow velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 0 publications
2
58
0
1
Order By: Relevance
“…The resulting lymphatic vessel images enable the visualization of the individual vessels with diameters of ~30-150 µm and the interconnection of the vessels to form a network. Previous studies have reported the diameters of the cutaneous lymphatic capillaries (37-76 µm) [28,29], which are broadly in agreement with our results. We hypothesize that the larger vessels identified in our images may be dilated in response to inflammation [1] attributed to the wound healing process [30].…”
Section: Discussionsupporting
confidence: 93%
“…The resulting lymphatic vessel images enable the visualization of the individual vessels with diameters of ~30-150 µm and the interconnection of the vessels to form a network. Previous studies have reported the diameters of the cutaneous lymphatic capillaries (37-76 µm) [28,29], which are broadly in agreement with our results. We hypothesize that the larger vessels identified in our images may be dilated in response to inflammation [1] attributed to the wound healing process [30].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, shear force levels in other postnatal lymphatics have been previously estimated. Under a basal physiological condition, the shear force level was approximately 0.64 dyn/cm 2 in a collecting lymphatic vessel (45), 0.001 dyn/cm 2 in mouse tail capillaries (46), and 0.003 dyn/cm 2 in human skin capillaries (47). Compared with these very low shear force levels, however, conceptual predicnology (43) and studied the impact of genetic ablation of Dtx3l on embryonic lymphatic development.…”
Section: Discussionmentioning
confidence: 99%
“…It is not likely that the persistence of brain homogenate in the lymphatics is simply due to a low rate of lymph flow in the nasal cavity, given that flow rates have been reported to average 3 to 9 m/s in different species (5,23,82) and that dye placed in the nose reaches cervical lymph nodes in 14 to 51 min, depending on the species (88). The presence of brain homogenate within lymphatics is consistent with their role of draining fluid and macromolecules from the extracellular matrix of the lamina propria in the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%